Impact Investing through Crowdlending: Examining the Role of Intermediation and the Potential for Development Banks - Andrew Lee; Christiane Weiland (Vierteljahrshefte zur Wirtschaftsforschung, 2020)
Development banks are facing changing market conditions with low interest rates, rapid technological change, and an increased interest in impact investment. This combination of factors challenges traditional processes and business models, but also provides a chance to develop new and sustained business opportunities. We examine examples of impact investment crowdfunding platforms in an international and domestic context. We evaluate their organisational structure, especially in connection with the potential integration of an intermediary and possible conflicts of interest. Our analysis provides both economic justification for activities of promotional and development banks in this area and new inputs for expanding their business model with a transparent and trustworthy financial lending instrument for small-scale retail investors. – – Förderbanken sehen sich verändernden Marktbedingungen mit niedrigen Zinssätzen, schnellem technologischen Wandel und einem erhöhten Interesse an Impact-Investitionen gegenüber. Dieses Umfeld stellt traditionelle Prozesse und Geschäftsmodelle in Frage, birgt aber auch eine Chance, neue und nachhaltige Geschäftsmöglichkeiten zu entwickeln. Wir betrachten Beispiele für Impact Investment Crowd-funding-Plattformen in einem internationalen und nationalen Kontext und evaluieren ihre Organisationsstruktur insbesondere im Hinblick auf die mögliche Einbindung eines Intermediärs und eventuelle Interessenkonflikte. Unsere Analyse liefert sowohl eine wirtschaftliche Rechtfertigung für die Aktivitäten von Förder- und Entwicklungsbanken in diesem Bereich als auch neue Inputs für die Erweiterung ihres Geschäftsmodells, indem sie ein transparentes und vertrauenswürdiges Anlageinstrument für Kleinanleger bereitstellen.
Keywords: G21; L3; L14; 330; Development banks; platform business models; crowdlending; impact investing; microfinance; intermediation